Subclinical Cardiovascular Presentation in Covid19: A Case Report - Hossien Shiebani; Homatash Saba (Institute of Medico-legal Publications Pvt Ltd, 2021)
The coronavirus disease 2019 (COVID-19), elicited by severe acute respiratory syndrome coronavirus 2(SARS-CoV-2) infection, is a pandemic public health emergency of global concern. Other than the profoundsevere pulmonary damage, SARS-CoV-2 infection also leads to a series of cardiovascular abnormalities,including myocardial injury, myocarditis and pericarditis, arrhythmia and cardiac arrest, cardiomyopathy,heart failure, cardiogenic shock, and coagulation abnormalities. mechanisms have been postulated forCOVID-19-associated cardiovascular damage including SARS-CoV-2 receptor angiotensin-convertingenzyme 2 (ACE2) activation, cytokine storm, hypoxemia, stress and cardiotoxicity of antiviral drugs. Inthis paper we reported a patient with severe Cocid 19 pnumonia that had very high level of Troponin Iwithout history of cardio vascular and other underlying diseases expect mild HTN with use of amlodipine.She had a ECG with old LBBB without significant ST-T bnormality and normal data in Trance thoracicechocardiography(TTE). We named this condition subclinical involvemet of cardiovascular system inCovid19 and our discussion is about reasons and origination of this Troponin elevation.